'Model-Platonism' in economics: on a classical epistemological critique. Issue 2 (21st February 2013) - KAPELLER, JAKOB
Abstract: Roughly 50 years ago, the eminent German philosopher and social scientist Hans Albert presented a critique of 'Model-Platonism' in economics to describe essential elements of the 'neoclassical style of economic reasoning'. Specifically, Albert advanced a series of epistemological arguments to illustrate conceptual shortcomings in neoclassical theory, which may be utilized to immunize the latter against conflicting empirical evidence. This article summarizes Albert's main arguments and illustrates his most important insights by using simple propositional logic. Based on these findings, a clarification and definition of 'Model-Platonism' is offered and the applicability of the Model-Platonism-critique to current developments in mainstream economics is assessed. Finally, two possible extensions of Albert's argument, the concepts of oscillating informational content and axiomatic variation, are illustrated with respect to their potential for immunization against critique.